Silver Triflate/N‐Fluorobenzenesulfonimide‐Catalyzed Cycloisomerization of Tryptamine‐Ynamide to Spiro[indoline‐3, 4′‐piperidine] Induced by Cation‐π‐π Interactions between Substrate and Metal Ligand. Issue 1 (26th November 2019) - Liang, Guoduan; Ji, Yanjun; Liu, Hairui; Pang, Yadong; Zhou, Bojun; Cheng, Maosheng; Liu, Yang; Lin, Bin; Liu, Yongxiang
Abstract: N ‐Fluorobenzenesulfonimide (NFSI), one of the most popular fluorinating agents in organic synthesis, was used as a ligand of silver triflate (AgOTf) to assist the trapping of the persistent spiroindoleninium intermediates by forming a weak noncovalent interaction between the substrate and metal ligand. The AgOTf/NFSI catalytic system was identified in the cycloisomerization of tryptamine‐ynamide to spiro[indoline‐3, 4′‐piperidine] derivatives. The substrate tolerances were demonstrated by various synthetic substrates and commercially available nucleophiles. A cation‐π‐π model was proposed to elucidate the mechanism of action based on the experimental observations and density functional theory (DFT) calculations. Abstract :